Organization of observations near underground shelters of burrowing carnivorans: a comparison of different methods - Nataliia Brusentsova; Volodymyr Yarotskiy (Theriologia Ukrainica, 2021)
Observations near the burrows gives rich material on the biology, intraspecific and interspecific interactions, and individual behaviour of animals. In our work, we considered four methods of observation (visual observations, visual observations with photo-fixation, video surveillance, and camera trapping) of burrowing carnivorans near their underground shelters. The research was conducted in spring and summer in different years in the period from 2004 to 2021 in open and forest habitats near burrows of badgers (Meles meles Linnaeus, 1758) and foxes (Vulpes vulpes Linnaeus, 1758).Visual observations are always associated with the presence of humans near the underground shelter of burrowing carnivorans for a long period of time. The researcher can be present only at one burrow at a time. The advantages of this method are that it is simple, cheap and allows for observing not only the burrow, but also the surrounding area. Complementing the data of visual observations with photographs largely increases their scientific value and informativeness. The use of camera traps minimizes human impact on animal behaviour, covers more underground shelters (depending on the number of devices) and collects more concentrated material than other methods. Camera trapping and video surveillance is also more convenient for the researcher, especially during the round-the-clock collection of data. This method however requires significant material costs and time to review and sort materials before data analysis. Data collection is limited to the working area of devices that do not always have time to capture animals when they pass very quickly. It is important under different environmental conditions to choose the optimal method of observation in order to study the animals effectively. In open biotopes during the organization of observations, there are difficulties with the installation of photo- and video equipment and its camouflage. In our opinion, the method of visual observations with photo-fixation remains relevant in conducting research near underground shelters of burrowing carnivorans under such conditions. The method of camera trapping is optimal for forest biotopes.